Various green manure-fertilizer combinations affect the soil microbial community and function in immature red soil - Xu, Jing; Si, Linlin; Zhang, Xian; Cao, Kai; Wang, Jianhong (Frontiers in Microbiology, 2023)
Green manure application is a common practice to improve soil fertility in China. However, the impact of different green manure-fertilizer combinations on the soil microbial communities in the low-fertility immature red soil in southern China remains unclear. In this study, we conducted a pot experiment using two common green manure crops, ryegrass (Lolium perenne L.) and Chinese milk vetch (Astragalus sinicus L.), along with a fallow treatment. We also considered three combined fertilizer management strategies, including mineral, humic acid, and organic manure fertilizers. We evaluated the soil microbial biomass, activity, communities, functional prediction and their correlation with soil properties during green manure growth and incorporation periods, to assess the potential alterations caused by different green manure and fertilizer combinations. Our findings indicate that green manure application, particularly in combination with organic fertilizers, increased the alpha diversity of the soil bacterial community, while the opposite trend was observed in the fungal community. The application of green manure altered the soil microbial communities during both growth and incorporation periods, especially the taxa that participate in carbon, nitrogen and sulfur cycles. Notably, ryegrass significantly increased the relative abundance of bacterial phylum Firmicutes and fungal phylum Ascomycota, whereas Chinese milk vetch significantly stimulated the bacterial phylum Acidobacteria and fungal phylum Glomeromycota. Compared with fallow treatments, green manure application significantly increased the soil pH by 4.1%–12.4%, and microbial biomass carbon by 29.8%–72.9%, regardless of the types of combined fertilizer. Additionally, the application of green manure resulted in a 35.6%–142.6% increase in urease activity and a 65.9%–172.9% increase in β-glucosidase activity compared to fallow treatments, while led to a 22.5%–55.6% decrease in catalase activity. Further analysis revealed that the changes in both bacterial and fungal communities positively correlated with soil pH, soil organic matter, total nitrogen and alkali hydrolyzed nitrogen contents. Moreover, the relationship between the soil microbial community and soil enzyme activities was regulated by the specific green manure species. In conclusion, our results provide insight into the effects of different green manure-fertilizer combinations on soil microorganisms and their underlying mechanisms in improving soil fertility in the low-fertility immature red soil.